Colorimetric and optical discrimination of halides by a simple chemosensor1. Issue 48 (28th May 2015) - Haque, Syed A.; Bolhofner, Robert L.; Wong, Bryan M.; Hossain, Md. Alamgir
<x xml:space="preserve">Abstract</x> A simple tripodal copper(ii) complex discriminates halides via a distinct color change for each halide in acetonitrile.